Zoonotic nematodes of wild carnivores. (August 2019) - Otranto, Domenico; Deplazes, Peter
Abstract: For a long time, wildlife carnivores have been disregarded for their potential in transmitting zoonotic nematodes. However, human activities and politics (e.g., fragmentation of the environment, land use, recycling in urban settings) have consistently favoured the encroachment of urban areas upon wild environments, ultimately causing alteration of many ecosystems with changes in the composition of the wild fauna and destruction of boundaries between domestic and wild environments. Therefore, the exchange of parasites from wild to domestic carnivores and vice versa have enhanced the public health relevance of wild carnivores and their potential impact in the epidemiology of many zoonotic parasitic diseases. The risk of transmission of zoonotic nematodes from wild carnivores to humans via food, water and soil (e.g., genera Ancylostoma, Baylisascaris, Capillaria, Uncinaria, Strongyloides, Toxocara, Trichinella ) or arthropod vectors (e.g., genera Dirofilaria spp., Onchocerca spp., Thelazia spp.) and the emergence, re-emergence or the decreasing trend of selected infections is herein discussed. In addition, the reasons for limited scientific information about some parasites of zoonotic concern have been examined. A correct compromise between conservation of wild carnivores and risk of introduction and spreading of parasites of public health concern is discussed in order to adequately manage the risk of zoonotic nematodes of wild carnivores in line with the 'One Health' approach. Graphical abstract: Image 1 Highlights: A large variety of wild carnivore nematodes have zoonotic potential. Limited epidemiological information is available for nematode zoonoses of wild carnivores. Some nematode zoonosis of wild carnivores may display a considerable morbidity. A compromise between animal conservation and zoonotic infection is advocated. Strict control of exotic carnivore species invading wildlife are urgently needed.